1985
DOI: 10.1002/bjs.1800720809
|View full text |Cite
|
Sign up to set email alerts
|

Acral (volar—subungual) melanoma

Abstract: Acral melanoma occurs in the volar surface of the hands, feet, fingers, toes and subungual sites. Recently it has been recognized as a distinct entity with characteristic clinical and pathological features. Of our 340 patients with malignant melanoma, 24 (7 per cent) had acral melanoma. Sixteen were in the plantar skin, two in the palms and six in the nailbed. The delay in diagnosis was 6 months to 5 years and most of the patients presented with large neglected tumours. Fourteen lesions had histological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…This is probably due to an earlier diagnosis after more public campaigns and to a more recent cohort of patients. As in the present studies, previous reports have demonstrated that most ALM occur on plantar sites and few on palmar sites, 4,6 , 7,15 , 16 also that subungual melanomas occur more often on the hands than on the feet. 17–20 …”
Section: Discussionsupporting
confidence: 86%
“…This is probably due to an earlier diagnosis after more public campaigns and to a more recent cohort of patients. As in the present studies, previous reports have demonstrated that most ALM occur on plantar sites and few on palmar sites, 4,6 , 7,15 , 16 also that subungual melanomas occur more often on the hands than on the feet. 17–20 …”
Section: Discussionsupporting
confidence: 86%
“…This difference has been attributed to the misdiagnoses and the delays in diagnosis that are common for plantar and subungual melanomas. Acral melanomas are often misdiagnosed or ignored before an accurate diagnosis is made [5,6]. Plantar melanomas are hidden from view and may be mistaken for warts, and subungual melanomas are often mistaken for subungual hematomas before the correct diagnosis is made [5].…”
Section: Introductionmentioning
confidence: 98%
“…AM is rare in Caucasians (1–7%) but has higher incidence in non-White individuals345678, accounting for up to 58% of all cutaneous melanomas in Asians9 and even more (60–70%) in Blacks10. It is often misdiagnosed or ignored before an accurate diagnosis is made because it is hidden from view1112. Furthermore, AM may represent a more biologically aggressive melanoma subtype and is thought to carry a worse prognosis when compared with other melanoma subtypes1213141516.…”
mentioning
confidence: 99%